Clinical translation of abdominal histotripsy: a review of preclinical studies in large animal models - Katrina L. Falk; Paul F. Laeseke; Meridith A. Kisting; Annie M. Zlevor; Emily A. Knott; Amanda R. Smolock; Charles Bradley; Eli Vlaisavljevich; Fred T. Lee; Timothy J. Ziemlewicz (International Journal of Hyperthermia, 2023)
AbstractHistotripsy is an emerging noninvasive, non-thermal, and non-ionizing focused ultrasound (US) therapy that can be used to destroy targeted tissue. Histotripsy has evolved from early laboratory prototypes to clinical systems which have been comprehensively evaluated in the preclinical environment to ensure safe translation to human use. This review summarizes the observations and results from preclinical histotripsy studies in the liver, kidney, and pancreas. Key findings from these studies include the ability to make a clinically relevant treatment zone in each organ with maintained collagenous architecture, potentially allowing treatments in areas not currently amenable to thermal ablation. Treatments across organ capsules have proven safe, including in anticoagulated models which may expand patients eligible for treatment or eliminate the risk associated with taking patients off anti-coagulation. Treatment zones are well-defined with imaging and rapidly resorb, which may allow improved evaluation of treatment zones for residual or recurrent tumor. Understanding the effects of histotripsy in animal models will help inform physicians adopting histotripsy for human clinical use.